A REVIEW ON LIGHTWEIGHT DESIGN AND CRASHWORTHINESS REQUIREMENTS OF THIN-WALLED TUBULAR STRUCYURE - HUO Peng; LI JianPing; XU ShuCai; YANG Xin; HUANG Han; FAN XiaoWen (Jixie qiangdu)
The research on crashworthiness of thin-walled tubular structures is one of the important researches in the fields of automotive engineering,aerospace and so on.Based on the analysis of material characteristics,structural characteristics and mathematical optimization models of thin-walled tubular structures,this paper expounds the internal relations of loading conditions,deformation modes,energy absorption characteristics and crashworthiness of different types of thin-walled tubular structures.It is proposed that the research on the crashworthiness of thin-walled tubular structures based on structural bionics is an important direction and research idea for future safety and energy-saving research.It provides reference for solving the challenge and the direction of future development in the current research stage.